EFFORTS TO INCREASE ENGLISH LEARNING ACHIEVEMENT WITH THE APPLICATION OF THE LEARNING MODEL JIGSAW COOPERATIVE - Arlinayanti, Kadek Dwi; Sariyani, Ni Nyoman; Gara, I Wayan (Universitas Pendidikan Ganesha, 2020)
This study aims to determine the improvement in English learning achievement of students of class XI IBB 2, SMA Negeri 1 Sukasada in the 2019/2020 Academic Year in the